ISLAMIC FUNDAMENTALIST AND NATIONALISM (STUDY AT DARUL MA’RIFAT ISLAMIC BOARDING SCHOOL, KEDIRI - EAST JAVA) - Reza Fahmi Haji Abdurrachim (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2016)
The Islamic Boarding School is always connected to the institution which produces the rebellions behavior and building radicalism in many Muslim countries, i.e Pakistan, Afghanistan, and Indonesia. The radicalism of Islam is always called Islamic Fundamentalist. The purposes of the research are (1) to describe the Islamic values which has been taught at Islamic Boarding School (especially at Darul Ma’rifat Islamic Boarding School at Kediri, East Java), (2) to describe the nationalism which has been taught at Darul Ma’rifat Islamic Boarding School at Kediri, East Java), (3) to describe the relation between Islamic Values which has been taught with nationalism of the students (santri) at Darul Ma’rifat Islamic Boarding School at Kediri, East Java. The research was based on quantitative studies. There were twelve thousand two hundred twenty seven pupils at Darul Ma’rifat Islamic Boarding School Kediri, East Java; however, only a few pupils has been involved in the research; three hundred and two pupils as a respondent. The data had been collected by observation, psychological scale, and documentation. The research found that there were correlation between Islamic values and Nationalism. So, although the pupils had been taught with the Islamic Values, the stick on the nationalism Islamic belief is very important to build peace and harmony for Indonesia. Then, they never thought that Islamic Values should be implemented without tolerance and respect to another religious belief. Penelitian ini didasari beberapa permasalahan; banyaknya kritik dan stigma sosial yang diberikan terhadap pesantren. Sebagai misalan, pesanteren selalunya dipersalahkan sebagai produsen terorist, mengajarkan ide Islam fundamentalis dan juga tak pernah membangunkan pemikiran nasionalisme kepada para pelajar (santri). Penelitian ini menggunakan metode pendekatan kuantitatif. Lokasi penelitian di Pondok Pesantern Moderen Darul Ma’rifat, Kediri Jawa Timur. Populasi dalam penelitian adalah seluruh santri di Ponpes tersebut. Sungguhpun demikian hanya 302 orang santri yang terlibat dalam penelitian ini. Teknik pengumpulan data dilakukan dengan observasi dan skala psikologi. Data dianalisa dengan model pendekatan statistik: korelasi pearson. Hasil : (1) Rata-rata sebaran dari pemikiran tentang fundamentalis para santri tergolong rendah. (2) Rata-rata sebaran dari pemikiran tentang nasionalisme yang dimiliki oleh para santri tergolong tinggi. (3) Ada hubungan antara pemikiran fundamentalis dan nasionalis di kalangan para santri. Tetapi pemikiran tentang fundamentalisme Islam hanya dipersepsikan bagaimana menjadi muslim yang baik dan berpegamng teguh pada nilai-nilai Islam. Kemudian para santri berfikir bahwa nasionalisme adalah sangat penting dalam masyarakat kita yang beragam suku bangsa dan membangun perdamaian –harmoni.